OXPIRT: Ontology-based eXpert system for Production of a generic Immediate Release Tablet - Chalortham,N. (2015)
We introduce an ontology based expert system for suggesting production of an immediately released tablet in generic version called OXPIRT. It was designed to assist pharmacists by providing a list of ingredients in formulation, a manufacturing process, a step-by-step instruction of laboratorial scale production for testing, and a validation in terms of pharmaceutical equivalence to the original drug. For practical usage and efficacy, the domain knowledge of an original drug and a generic drug production from a regulated guidebook and expired patents is represented in ontology format while the operational knowledge for calculating a formulation and suggesting a manufacturing process is given in the production rules. Experiments were conducted on four drugs to approve its capability, and we found that the system worked very well on recommending a generic table production in an actual situation. © 2013 Woodhead Publishing Limited. All rights reserved.